Immune related proteins and tumor infiltrating CD8+ lymphocytes in hypopharyngeal cancer in relation to human papillomavirus (HPV) and clinical outcome. Issue 11 (1st July 2020) - Landin, David; Ährlund‐Richter, Andreas; Mirzaie, Leila; Mints, Michael; Näsman, Anders; Kolev, Aeneas; Marklund, Linda; Dalianis, Tina; Munck‐Wikland, Eva; Ramqvist, Torbjörn
Abstract: Background: Hypopharyngeal cancer (HPSCC) shows a poor clinical outcome, while HPSCC, caused by human papillomavirus (HPV), presents a better outcome. Here, HPCC, immune proteins, and tumor infiltrating CD8+ lymphocytes (CD8+ TILs) were evaluated in relation to HPV and outcome. Methods: Fresh frozen tissue from four HPV‐positive HPSCC, 39 HPV‐negative HPSCC, and normal samples were analyzed for protein expression by the Proseek immuno‐oncology immunoassay. CD8+ TIL numbers evaluated by immunohistochemistry on 144 formalin‐fixed biopsies were analyzed in relation to clinical outcome. Results: Proteins differing between HPV‐positive and negative HPSCC included CD8A, PD‐L1, Fas ligand, and chemokines. High CD8+ TIL numbers were correlated to improve clinical outcome in HPV‐negative HPSCC. Conclusions: High expression of immune proteins in HPV‐positive HPSCC may explain the better clinical outcome. CD8+ TILs are of relevance for outcome of HPV‐negative HPSCC, while tumors with high immune activity but poor patient survival suggest a role for immune therapy.